Regulating damage clauses in (labor) contracts - Gerd Muehlheusser (Institute for the Study of Labor (IZA), 2006)
We analyze the role of damage clauses in labor contracts using a model in which a worker may want to terminate his current employment relationship and work for another firm. We show that the initial parties to a contract have an incentive to stipulate excessive damage clauses, which leads to ex post inefficiencies. This result is due to rent seeking motives a) between the contracting parties vis-à-vis third parties and b) among the contracting parties themselves. We then show that, by imposing an upper bound on the amount of enforceable damages, a regulator can induce a Pareto improvement; in some cases even the first best can be achieved
urn:nbn:de:101:1-20090406316
Keywords: 330; Arbeitsvertrag; Vertragsrecht; Rent Seeking; Verhandlungstheorie